PERSPECTIVES OF USING NATURAL FULLERENE CONTAINING MINERAL SHUNGITE IN WATER PROSSESSING - Мосин, О. В.; Игнатов, И. И. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2013)
In present paper the composition and structural properties of amorphous, uncrystallized, fulleren analogious carbon containing natural mineral - shungite, from deposit “Zazhoginskoe” in Karelia (Russian Federation), possessing high absorptional, catalitic and bactericidal activity are submitted. There are given data about nanostructure, obtained with the using of scanning electronic microscopy, and physico-chemical properties of this mineral. Prospects of using shungite as a sorbent in water-prosrssing and water purification and other industries are demonstrated.